Emerging Therapies for Acute Coronary Syndromes - Lilly, Scott M.; Wilensky, Robert L. (Frontiers in Pharmacology, 2011)
In the majority of cases acute coronary syndromes (ACS) are caused by activation and aggregation of platelets and subsequent thrombus formation leading to a decrease in coronary artery bloodflow. Recent focus on the treatment of ACS has centered on reducing the response of platelets to vascular injury as well as inhibiting fibrin deposition. Novel therapies include more effective P2Y12 receptor blockers thereby reducing inter-individual variability, targeting the platelet thrombin receptor (protease activated receptor 1) as well as directly inhibiting factor Xa or thrombin activity. In this review we discuss the clinical data evaluating the effectiveness of these various new ACS treatment options.